Innovative Didactic Approaches to the Development of Intercultural Competence in Spanish Language Teaching in Uzbekistan - Anastasiya Aleksandrovna Tkacheva (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article analyzes innovative didactic approaches used to develop intercultural competence in Spanish language teaching in the higher education institutions of Uzbekistan. The study focuses on modern pedagogical strategies that integrate cultural content, digital resources, and communicative activities in language instruction. It is argued that the use of interactive technologies, authentic cultural materials, and project-based learning significantly contributes to the formation of students’ intercultural communication skills and cultural awareness.